From Effectuation to Empowerment: Unveiling the Impact of Women Entrepreneurs on Small and Medium Enterprises’ Performance—Evidence from Indonesia - Sherly Theresia; Sabrina Oktaria Sihombing; Ferdi Antonio (Administrative Sciences)
Women entrepreneurs in small to medium enterprises (SMEs) in emerging countries play an essential role in the economy of developing countries such as Indonesia. Drawing on the resource-based view and entrepreneurship effectuation theory, this study examines how women’s entrepreneurial effectuation (WEE) modeled as a higher-order construct (HOC) comprising its four dimensions (LOCs)—namely, flexibility, experimentation, affordable loss, and pre-commitment—can influence employee performance (EMPRF) mediated by structural (STREM) and psychological empowerment (PSYEM). Using a disjointed two-stage PLS-SEM approach with data from 218 female SME employees, our results confirm that flexibility is the most salient effectuation dimension. WEE strongly predicts both STREM and PSYEM but shows no direct impact on EMPRF, highlighting that effectuation must be activated via empowerment mechanisms. PSYEM emerges as the strongest mediator of WEE on EMPRF, with STREM also contributing significantly and being amplified by gender equality practices; market orientation, by contrast, fails to moderate any paths. Theoretically, these findings enrich resource-based view (RBV) theory by integrating entrepreneurial effectuation dimensions and empowerment as human resource capabilities that generate inimitable performance gains. Practically, they suggest that women-led SMEs should integrate effectuation heuristics with targeted empowerment programs to realize the full potential of their human capital.